Analysis of Service Recovery, Behavioral Outcome and Recovery Paradox for Telkomsel Customers - Sari, Karmila (Journal of Science and Education (JSE), 2024)
Customer satisfaction is crucial to the success of a business. Service recovery is a response to errors committed by the firm that adversely affect the relationship between the company and the client. Customer perceptions of service recovery are explained in perceived justice in procedural justice, interactional justice, and distributive justice so that it can be seen directly in its influence on behavioral outcomes, namely trust, WOM (Word of Mouth), and loyalty. All of these elements can measure customer satisfaction with the products and services provided by Telkomsel. So, after researching 137 Telkomsel respondents, it was found that service recovery significantly influenced three perceived justice, namely procedural justice, interactional justice, and distributive justice, on complainant satisfaction. Where procedural justice contributes the most to complainant satisfaction with service recovery, while distributive justice contributes enough to implement service recovery, other than distributive justice only contributes a little. For behavioral outcomes on complainants who get service recovery, they tend to do WOM compared to having trust and loyalty. Meanwhile, the behavioral outcome of satisfied complainants has a higher trust than that of dissatisfied complainants. Dissatisfied complainants tend to do WOM compared to satisfied complainants. The behavioral outcome of satisfied complainants is much higher than the trust of satisfied complainants. This point indicates a recovery paradox. Meanwhile, WOM and loyalty in satisfied complainants and satisfied non-complainants have values that are not too different. From this research, the author assesses from the view of Telkomsel customers that service recovery is successful if the beginning of the system stage (procedural justice) is done correctly. Meanwhile, excellent handling of service recovery implementation maintains the company's image from the impact of negative WOM. Moreover, there are indications of a recovery paradox, indicating that Telkomsel still has opportunities to increase customer satisfaction. Service to customers who complain must be maintained to help determine customers' ever-changing needs and assess the company's performance so far.